Identification of pathogenicity determinants in ToLCNDV and their RNAi-based knockdown for disease management in Nicotiana benthamiana and tomato plants - Sarkar, Mehulee; Gupta, Dipinte; Singh, Oinam Washington; Paul, Samrat; Kumar, Ravinder; Mandal, Bikash; Roy, Anirban (Frontiers in Microbiology, 2024)
Begomovirus solanumdelhiense (tomato leaf curl New Delhi virus, ToLCNDV), is member of the genus Begomovirus, family Geminiviridae, is a prolific bipartite whitefly transmitted begomovirus in the Indian sub-continent has a wide host range, including solanaceous, cucurbitaceous and other plants. Recently, dsRNA-mediated non-transgenic approaches have been promising in managing plant viruses. Such an approach could be effective if the pathogenicity determinants of a virus are targeted. In the case of ToLCNDV, viral pathogenicity has been demonstrated with coat protein (AV1), pre-coat protein (AV2), transcription activator protein (AC2) and nuclear shuttle protein (NSP). In the present study, we investigated the involvement of the three RNA silencing suppressor proteins (AV2, AC2, AC4) encoded by ToLCNDV in pathogenicity determinants through transient overexpression and hairpin RNAi-based knockdown assays in Nicotiana benthamiana plants. Further, we showed that the transcripts of AV2, AC2, and AC4 genes can systemically move and express their proteins. Hairpin RNAi constructs targeting each pathogenicity determinant could effectively reduce symptom development and virus titer upon inoculation of ToLCNDV in N. benthamiana plants. Exogenous application of dsRNA individually (dsAV2/dsAC2/dsAC4) or together (cocktail dsRNA: dsCk) against the pathogenicity determinants showed a significant reduction of viral load and reduced severity of disease in plants treated with dsCk followed by dsAC4. The present report reconfirms that the RNA silencing suppressor proteins encoded by DNA-A genomic component of ToLCNDV, can also act as pathogenicity determinants. Further, we demonstrated for the first time that exogenous application of dsRNA targeting those pathogenicity determinants reduces ToLCNDV load and limits symptom development in tomato plants.